STRUCTURAL AND SEMANTICAL PECULIARITIES OF VOCABULARY FOR THE HUMAN APPEARANCE DESCRIPTION (A CASE STUDY OF ENGLISH LANGUAGE) - Пабат, Марина; Финчук, Галина (SWorldJournal, 2020)
This article investigates the specificity of using and the features of estimated lexicon, particularly adjectives. The following categories of assessment, as a sign of femininity/masculinity in the human characteristics, specificity of zoomorphism and zoo